Effect of adhesive layer thickness and slant angle on piezoelectric bonded joints / Somnath Somadder and Md. Shahidul Islam - Islam, Md. Shahidul; Somadder, Somnath (Universiti Teknologi MARA, 2022)
Piezoelectric materials have found their parts in numerous manufacturing applications such as transducers and sensors. Piezoelectric material shows anisotropy; in addition, its elastic field and electric field are integrated. The analysis of piezoelectric materials has obtained great interest among researchers with the development of smart structures. It is significant to explain the distribution of stress and electric displacement fields along the bonded edge. It has never been obvious how stress singularity and electric displacement fields are distributed at the vertex of piezoelectric dissimilar material joints. Stress and electric displacement distribution near the vertex along the interface of piezoelectric boned joints are investigated in this present research. Numerical analysis of piezoelectric dissimilar material joints is carried out by using Abaqus FEA software. From the numerical analysis, it is observed that stress, displacement, electric potential, electric displacement field evolvement along the interface edge rises with the increment of adhesive layer thickness and slant angle. So, a thin adhesive layer thickness and small slant angle are more reliable for operation.